2022
DOI: 10.20945/2359-3997000000433
|View full text |Cite
|
Sign up to set email alerts
|

DKA and new-onset type 1 diabetes in Brazilian children and adolescents during the COVID-19 pandemic

Abstract: We assess the severity and frequency of diabetic ketoacidosis (DKA) in new-onset type 1 diabetes mellitus (T1D) patients and in patients with previous diagnosis of T1D in a referral Brazilian university hospital in the first five months of the COVID-19 pandemic. We also compare the data with data from pre-pandemic periods. Forty-three new-onset T1D patients were diagnosed between April and August of the years 2017, 2018, 2019, and 2020. During the COVID-19 pandemic, the number of newonset T1D was over twice th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Asimismo, un estudio realizado en Alberta, Canadá, informó que la prevalencia de DM1 se mantuvo relativamente estable durante la pandemia de COVID-19 comparada con la prepandemia 19 . Por el contrario, un estudio desarrollado durante la pan-demia en Brasil enontró que las tasas de debuts de DM1 fueron más del doble que las tasas de debuts observados en los 3 años previos 20 . Además, estos estudios describieron un fuerte aumento en los debuts de DM1 en niños que residían en regiones muy afectadas por la pandemia de COVID-19 3,4 .…”
Section: Discussionunclassified
“…Asimismo, un estudio realizado en Alberta, Canadá, informó que la prevalencia de DM1 se mantuvo relativamente estable durante la pandemia de COVID-19 comparada con la prepandemia 19 . Por el contrario, un estudio desarrollado durante la pan-demia en Brasil enontró que las tasas de debuts de DM1 fueron más del doble que las tasas de debuts observados en los 3 años previos 20 . Además, estos estudios describieron un fuerte aumento en los debuts de DM1 en niños que residían en regiones muy afectadas por la pandemia de COVID-19 3,4 .…”
Section: Discussionunclassified
“…The incidence of T1DM in children from Lower Silesia during the COVID-19 pandemic was compared with previous years, and their clinical status (incidence of DKA, the mean pH upon at admission) at the time of diagnosis was worse during the pandemic than prior to it. A study from Southeastern Brazil revealed a higher incidence and severity of new onset T1DM cases with DKA during the pandemic period ( 20 ). Lawrence et al ( 21 ) compared new onset pediatric T1DM patients during the pandemic to those presenting in the previous 5 years and showed an increased incidence of severe DKA during pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Data about the prevalence of diabetic ketoacidosis (DKA) are much more concordant in the literature. Several cohort studies [ 91 , 93 , 98 , 102 , 106 , 123 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ] and two meta-analyses [ 114 , 164 ] report increases in DKA frequency and DKA severity at diagnosis among newly diagnosed T1D patients. A multicenter study, involving 13 national diabetes registries (Australia, Austria, Czechia, Denmark, Germany, Italy, Luxembourg, New Zealand, Norway, Slovenia, Sweden, the USA (Colorado), and Wales) compared the observed DKA prevalence in children and adolescents in 2020 and 2021 to predictions based on trends over the prepandemic years 2006–2019.…”
Section: Diabetesmentioning
confidence: 99%